Digital Readiness of Zakat Management Organization in West Sumatera - Putra, Gusti Dirga Alfakhri; Wira, Ahmad; Novia, Aidil (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2023)
Abstract. This study evaluates the digital readiness of private and community-owned zakat management organizations in West Sumatra. The research uses the digital readiness index developed by the National Amil Zakat Agency and the Department of Sharia Economics of Bank Indonesia. A quantitative approach and a multi-stage weighted index calculation method are utilized. The sample consists of eight private zakat management organizations in West Sumatra with operational permits from the Regional Office of the Ministry of Religious Affairs. The results indicate that the overall digital readiness of zakat management organizations in West Sumatra is very good. The collection dimension shows a high level of digitalization readiness, while the distribution, utilization, and reporting dimensions also received a very good rating. Six of the eight institutions fall into the very good category when evaluated individually, while the remaining two are classified as good. With these results, zakat management can be optimized in various aspects. Abstrak. Penelitian ini mengkaji kesiapan digital organisasi pengelola zakat swasta di Sumatera Barat, dengan menggunakan indeks kesiapan digital yang dikembangkan oleh Badan Amil Zakat Nasional dan Departemen Ekonomi Syariah Bank Indonesia. Pendekatan kuantitatif digunakan bersama dengan multi-stage weighted index calculation. Sampel terdiri dari delapan organisasi pengelola zakat swasta di Sumatera Barat yang memiliki izin operasional dariKantor Wilayah Kementerian Agama. Hasil penelitian menunjukkan bahwa secara keseluruhan kesiapan digital organisasi pengelola zakat di Sumatera Barat sangat baik. Dimensi pengumpulan menunjukkan tingkat kesiapan digitalisasiyang tinggi. Sementara dimensi pendistribusian, pendayagunaan, dan pelaporan juga berada pada level sangat baik. Enam dari delapan lembaga masuk dalam kategori sangat baik jika dievaluasi secara individual, sedangkan dua sisanyatergolong baik. Dengan hasil tersebut, pengelolaan zakat dapat dioptimalkan pada berbagai aspek.